An investigation of a novel anomalous pink feather colouration in the Mute Swan Cygnus olor in Britain and Ireland - O’Connell, Merita M; Keating, Usna; Mcelligott, Deirdre; O’Reilly, Paddy; O’Callaghan, Julianna; O’Halloran, John (Wildfowl, 2013)
Pink feather colouration in normally white adult Mute Swans Cygnus olor is described here for the first time. Symmetrical salmon-pink colour was first evident on primary feather tips after moult (July–August), spread to secondary and tertiary remiges as the year progressed, darkened as winter approached, and sometimes developed to a brown colour. Affected feathers tended to become brittle, fragmented and lose their ability to repel water. Surveys made at nine sites in Britain and Ireland between May 2003 and January 2009 found 12–85% of swans with pink coloration. Highest prevalence occurred amongst flocks dependent on artificial food on eutrophic water bodies. Feather samples (white and pink), bill swabs and swabs of uropygial oil collected from swans in the field, and also pink fungus isolated from a bread sample, were cultured and subjected to high performance liquid chromatography (HPLC), to identify organisms and pigments respectively. Salmon-pink Chrysonilia sitophila fungus colonies developed on agars inoculated with samples from swans at Cork Lough and from the bread sample, but were absent from those inoculated with samples from swans at Lough Aderry and Rostellan Lake, where the birds feed mainly on aquatic vegetation. HPLC revealed that the dominant pigments in pink feathers were generally consistent with those found in C. sitophila, indicating that C. sitophila is the most likely agent responsible for the pink colour on swan plumage. Field experiments implied that C. sitophilawas not transferred to the plumage through contact with water; we therefore suggest that C. sitophila is acquired through exposure to contaminated food via the bill and is preened onto the plumage. A layer of environmental contaminants and debris that coats the plumage of swans inhabiting eutrophic water bodies may provide a substrate for fungal growth.